Robust Physically-Constrained Modeling of the Mitral Valve and Subvalvular Apparatus - Voigt, Ingmar; Mansi, Tommaso; Ionasec, Razvan Ioan; Assoumou Mengue, Etienne; Houle, Helene; Georgescu, Bogdan; Hornegger, Joachim; Comaniciu, Dorin (Proceedings of the 14th International Conference on Medical Image Computing and Computer Assisted Intervention, 2011)
Mitral valve (MV) is often involved in cardiac diseases, with various pathological patterns that require a systemic view of the entire MV apparatus. Due to its complex shape and dynamics, patient-specific modeling of the MV constitutes a particular challenge. We propose a novel approach for personalized modeling of the dynamic MV and its subvalvular apparatus that ensures temporal consistency over the cardiac sequence and provides realistic deformations. The idea is to detect the anatomical MV components under constraints derived from the biomechanical properties of the leaflets. This is achieved by a robust two-step alternate algorithm that combines discriminative learning and leaflet biomechanics. Extensive evaluation on 200 transesophageal echochardiographic sequences showed an average Hausdorff error of 5.1 mm at a speed of 9 sec, which constitutes an improvement of up to 11.5% compared to purely data driven approaches. Clinical evaluation on 42 subjects showed, that the proposed fully-automatic approach could provide discriminant biomarkers to detect and quantify remodeling of annulus and leaflets in functional mitral regurgitation.
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD5.robust_1